2019
DOI: 10.1590/s1519-9940200362019
|View full text |Cite
|
Sign up to set email alerts
|

Citrus pulp-based supplement reduces the detrimental effects of high grazing pressure on the performance of beef cattle under a rotational system of Urochloa brizantha

Abstract: SUMMARY The objectives were to evaluate the performance of bull calves under two grazing strategies and the use of energy supplementation in a rotational system of marandu palisade grass (Urochloa brizantha) and to assess the morphological and chemical composition of the grass. Eighty eight-month-old bulls of 224 ± 2.4 kg body weight (BW) were used in a completely randomized block design in a 2×2 factorial arrangement of two post-grazing heights (i.e.10 cm or 15 cm) and of a citrus pulp-based supplement (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In the current study, animals supplemented at 0.5% LW gained in average 0.76 kg per day, similar to the liveweight performance of growing bulls under a rotational grazing system observed by Costa et al [ 1 ], using the same supplement allowance and management based on sward heights of 25 cm at the start and 10 cm post-grazing. Based on the equations of Marcondes et al [ 32 ], grazing Nellore bulls of 350 kg of LW with a DM intake of 2.2% of LW and consuming about 4.75 kg TDN/day would have an ADG of 1.0 kg.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In the current study, animals supplemented at 0.5% LW gained in average 0.76 kg per day, similar to the liveweight performance of growing bulls under a rotational grazing system observed by Costa et al [ 1 ], using the same supplement allowance and management based on sward heights of 25 cm at the start and 10 cm post-grazing. Based on the equations of Marcondes et al [ 32 ], grazing Nellore bulls of 350 kg of LW with a DM intake of 2.2% of LW and consuming about 4.75 kg TDN/day would have an ADG of 1.0 kg.…”
Section: Discussionsupporting
confidence: 86%
“…In this context, the utilization of by-products such as citrus pulp replacing corn, an ingredient heavily utilised in human nutrition, represents an important factor in increasing sustainability on the intensification of ruminant production systems. Costa et al [ 1 ] found that a citrus pulp-based supplement helped animals maintain performance under high grazing pressure in a rotational system of Urochloa brizantha during the wet season, whilst in the current experiments, corn and citrus pulp-based supplements were used in the transition period, when both quality and amount of forage produced decrease.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the rainy season, there is a range of responses regarding animal performance with the use of supplementation, as in this period the feasibility of this technique depends on the balance between the supplement characteristics and nutrients available in the pasture, controlled by grazing management strategies, which can define the level of performance of animals (Costa et al, 2019;Ziemniczak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%